A Novel Multiepitope Vaccine for Jembrana Disease: Immunoinformatics, Structural Analysis, Molecular Docking, and Molecular Dynamics - Fatimah, Fatimah; Wibowo, Syahputra; Sari, Dini Wahyu Kartika; Pratiwi, Rarastoeti; Kusumawati, Asmarani (Universitas Gadjah Mada, 2026)
Jembrana disease, caused by the Jembrana virus, leads to high mortality (30%) and abortion (49%) in cattle, making vaccination essential. In this study, a multiepitope vaccine was designed using immunogenic TM and CA proteins. Predicted cytotoxic T lymphocyte, helper T lymphocyte, and linear B-cell epitopes were linked with flexible linkers, and the 50S L7/L12 ribosomal protein was added as a TLR4 agonist. In silico analysis confirmed the construct as non-allergenic, antigenic, and thermostable (aliphatic index 85.44), with 94.2% of residues in favored Ramachandran regions. Docking analysis revealed strong binding to TLR4 (−66 kcal/mol), and molecular dynamics simulations validated the structural stability. Immune simulations revealed increased antigen and antibody levels (IgM early, IgG1/IgG2 after day 15), progressive CD4+ T-helper expansion, transient CD8+ T-cell peaks, elevated IFN-γ and IL-2, and strong dendritic cell activation through MHC I and II pathways. These findings indicate the vaccine effectively stimulates humoral and cellular responses, supporting its potential as a promising candidate against the Jembrana virus.